PENGARUH KREDIBILITAS INFLUENCER DAN ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP KEPUTUSAN PEMBELIAN PRODUK MUSTIKA RATU PADA MAHASISWA UNIVERSITAS DIPONEGORO - Berliana Zahra Aurelia; Saryadi Saryadi; Sudharto Prawoto Hadi (Jurnal Ilmu Administrasi Bisnis, 2025)
The emergence of many new cosmetic brands that actively utilize digital marketing has intensified business competition in Indonesia's beauty and cosmetics sector. One of the local brands, Mustika Ratu, experienced a fluctuating sales, which may be caused by factors such as the credibility of influencers and electronic word of mouth (e-WOM). This study aims to determine the influence of Influencer Credibility and Electronic Word of Mouth (e-WOM) on the Purchase Decisions of Mustika Ratu products. The research method used is explanatory research. The respondents in this study were selected using non-probability sampling with a purposive sampling technique. The sample consisted of 96 students from Diponegoro University who accessed reviews of Mustika Ratu products on digital platforms or from influencers and had purchased Mustika Ratu products. Data was collected through a questionnaire and analyzed using SPSS version 25.0 software.The results show that Influencer Credibility affects Purchase Decisions, as does Electronic Word of Mouth (e-WOM) on Mustika Ratu product Purchase Decisions. Based on the results of the study, it is recommended that Mustika Ratu collaborate with influencers, enhance social media activity, develop programs that encourage consumers to write product reviews, and foster positive electronic word of mouth.